Recent Advances in Nanobiotechnology: Applications in Medicine, Environmental Science, and Industry - B. Narasimha Rao; Y. Kavya; P. Vanaja; R. Balaji; S. Afzal; V. Suresh; N. Raghavendra Naveen (Current Nanomedicine, 2026)
Nanobiotechnology is an interdisciplinary field that integrates nanotechnology with biological sciences to develop nanoscale tools and systems with transformative applications in medicine, environmental science, and industry. By leveraging the unique properties of nanomaterials- such as high stability, enhanced reactivity, tunable surface chemistry, and precise functionalization- nanobiotechnology facilitates groundbreaking innovations in targeted drug delivery, diagnostics, regenerative medicine, and biosensing. In medicine, nanocarriers, including liposomes, dendrimers, and polymeric nanoparticles, have revolutionized drug delivery by enhancing bioavailability, reducing systemic toxicity, and enabling controlled drug release, particularly in cancer therapy and gene therapy. Moreover, nanomaterials such as quantum dots and gold nanoparticles (AuNPs) contribute to early disease detection through advanced imaging and biosensing techniques. In regenerative medicine, nanostructured scaffolds mimic the extracellular matrix, promoting tissue repair and wound healing. Beyond healthcare, nanobiotechnology plays a pivotal role in environmental applications, including water purification, soil remediation, and pollution control, through nano-bioremediation strategies that employ nanocatalysts and biopolymer-based nanomaterials. Industrial applications range from the development of nanobiosensors for food safety monitoring to the synthesis of high-performance nanocomposites for sustainable energy solutions. This review provides a comprehensive overview of recent advancements in nanobiotechnology, discussing its impact on healthcare, environmental science, and industry. It also addresses the challenges of biocompatibility, large-scale production, and regulatory hurdles, which must be overcome to unlock the full potential of nanobiotechnology. As research continues to progress, the integration of artificial intelligence and machine learning with nanobiotechnology is expected to further enhance precision, efficiency, and applicability in diverse scientific and technological domains.